Hypercoagulation Detected by Rotational Thromboelastometry Predicts Mortality in COVID-19: A Risk Model Based on a Prospective Observational Study - Almskog, Lou M.; Wikman, Agneta; Svensson, Jonas; Bottai, Matteo; Kotormán, Mariann; Wahlgren, Carl-Magnus; Wanecek, Michael; van der Linden, Jan; Ågren, Anna (TH Open, 2022)
Background Severe disease due to the novel coronavirus disease 2019 (COVID-19) has been shown to be associated with hypercoagulation. The aim of this study was to assess the Rotational Thromboelastometry (ROTEM) as a marker of coagulopathy in hospitalized COVID-19 patients.Methods This was a prospective, observational study where patients hospitalized due to a COVID-19 infection were eligible for inclusion. Conventional coagulation tests and ROTEM were taken after hospital admission, and patients were followed for 30 days. A prediction model, including variables ROTEM EXTEM-MCF (Maximum Clot Firmness) which in previous data has been suggested a suitable marker of hypercoagulation, age, and respiratory frequency, was developed using logistic regression to evaluate the probability of death.Results Out of the 141 patients included, 18 (13%) died within 30 days. In the final prediction model, the risk of death within 30 days for a patient hospitalized due to COVID-19 was increased with increased EXTEM-MCF, age, and respiratory frequency. Longitudinal ROTEM data in the severely ill subpopulation showed enhanced hypercoagulation. In an in vitro analysis, no heparin effect on EXTEM–coagulation time (CT) was observed, supporting a severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) effect on prolonged initiation of coagulation.Conclusion Here, we show that hypercoagulation measured with ROTEM predicts 30-day mortality in COVID-19. Longitudinal ROTEM data strengthen the hypothesis of hypercoagulation as a driver of severe disease in COVID-19. Thus, ROTEM may be a useful tool to assess disease severity in COVID-19 and could potentially guide anticoagulation therapy.
Keywords: COVID-19; thromboelastometry; coagulopathy; thrombosis; mortality